Remote Regions in Geography Education. A Synopsis of Factors Influencing Geography Lessons - Breitbach, Thomas (Journal of Geography Education, 2007)
Knowledge of remote regions and countries is an important topic of geographical education. Due to rapid changes all over the world and global challenges on the one hand and a lot of changes in school education on the other hand the task of teaching the geography of remote regions is facing many problems. The following essay presents some results of an investigation into this topic which aims at developing recommendations and guidelines for teachers and students to deal with the multitude of questions connected to the topic. This investigation analyses the factors influencing this particular field of geographical education at school (ger. Unterrichtliche Entscheidungsfelder) and puts emphasis on the question in what way these factors influence each other. The analysis shows that problems such as over-simplification, distortion of facts, stereotypes and lack of insight into possible solutions still exist in modern concepts. However, they are mostly not due to theoretical problems but to deficiencies in everyday teaching and the supply of information because lessons and schoolbooks are often influenced by topical trends that emphasize one aspect but neglect other aspects of a topic. The study proved that the complex situation of teaching remote regions cannot be described and evaluated by means of simple input-output strategies and monostructural studies of efficiency but that decisions as well as judgements within the learning process have to made on the basis of the complexity of the systems, standards of ethics and a "feeling" for the requirements of a particular group of learners at a particular time.